The mediating role of green procurement on the relationship between environmental knowledge and procurement sustainability: empirical study of firms in the western region of ghana - ENNIN, MICHAEL (KNUST, 2024)
A thesis submitted to the department of supply chain and information systems, institute of distance learning, Kwame Nkrumah university of science and technology, in partial fulfilment of the requirements for award of the degree of master of science procurement and supply chain management